PsEst3, a new psychrophilic esterase from the Arctic bacterium Paenibacillus sp. R4: crystallization and X-ray crystallographic analysis - Kim, Hyun (Acta Crystallogr F Struct Biol Commun, 2018)
Esterases are very useful biocatalysts in industry: they hydrolyze esters and split them into a carboxylic acid and an alcohol. The psychrophilic esterase PsEst3 was obtained from Paenibacillus sp. R4, which was isolated from the active layer of the permafrost in Council, Alaska. PsEst3 was successfully overexpressed using a psychrophilic chaperonin co-expression system and was purified by nickel-affinity and size-exclusion chromatography. Recombinant PsEst3 was crystallized at 290 K using the hanging-drop vapour-diffusion method. X-ray diffraction data were collected to 2.1 Å resolution. The crystal was determined to belong to space group P4(1)32 or P4(3)32, with unit-cell parameters a = b = c = 145.33 Å. Further crystallographic analysis needs to be conducted to investigate the structure and function of this esterase.